Giant lacustrine pockmarks with subaqueous groundwater discharge and subsurface sediment mobilization. Issue 9 (13th May 2015) - Reusch, Anna; Loher, Markus; Bouffard, Damien; Moernaut, Jasper; Hellmich, Franziska; Anselmetti, Flavio S.; Bernasconi, Stefano M.; Hilbe, Michael; Kopf, Achim; Lilley, Marvin D.; Meinecke, Gerrit; Strasser, Michael
Abstract Subsurface fluid flow in oceans and lakes affects bathymetric morphology, sediment distribution, and water composition. We present newly discovered giant lacustrine pockmarks in Lake Neuchâtel (up to 160 m diameter and 30 m deep) that rank among the largest known pockmarks in lakes. Our multidisciplinary study reveals ~60 m of suspended sediment inside a pockmark. The sediment suspension is 2.6° warmer and isotopically lighter in δ18OH2O by 1.5‰ than the ambient lake water, documenting currently active fluid flow by karstic groundwater discharge from the Jura Mountain front into the Swiss Plateau hydrological system. Strikingly, the levees of the pockmarks comprise subsurface sediment mobilization deposits representing episodic phases of sediment expulsion during the past. They strongly resemble subsurface fluid flow features in the marine realm. Comparable processes are expected to also be relevant for other carbonate‐dominated mountain front ranges, where karstic groundwater discharges into lacustrine or marine settings.